Konstruksi Identitas Komunitas Pustaka Jalanan Surabaya - Mukadar, Mohamad Fauzan Ismail; Candrasari, Yuli (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to find out the management of impression of the Pustaka Jalanan Surabaya community. To answer the problem above, this research uses the theory of impression management within Goffman's Dramaturgy Theory. This research uses dramaturgy theory to find out how the front stage of Pustaka Jalanan Surabaya which is formed by its members using impression management to reach their goals. This study uses a constructivist paradigm with a qualitative approach and phenomenological methods, research subjects are members of Pustaka Jalanan Surabaya by using the snowball technique obtained by 3 (three) informants. The data collection techniques used are: literature study, interview depth, observation, and documentation. The result of this research is that informants show their concern about the public's perception of punk and want to show that they are the real punk. The informants paid attention to what the groups were doing outside of the main activities of Pustaka Jalanan Surabaya, namely discussions and drinking alcohol. This affects the informant as a party who adapts to the groups to take part in this activity. There is impression management in the Pustaka Jalanan Surabaya community to achieve their goals. This affects the public perception of Punk in Pustaka Jalanan Surabaya. The impression management that occurs is the formation of the front stage by hiding things that are considered unacceptable by the public on the back stage. Keywords: Impression Management, Dramaturgy Identity Theory, Phenomenology, Punk